Polar Vortex Conditions During the 1995-96 Artic Winter: Meteorology and MLS Ozone - Manney, G.; Santee, M.; Froidevaux, L.; Waters, J.; Zurek, R. (2004)
The 1995-96 northern hemisphere (NH) winter was colder than any of the previous 17 NH winters, with temperatures continuously below the type 1 polar stratospheric cloud (PSC) threshold for over 2 1/2 months; upper tropospheric ridges in late Feb and early Mar 1996 led to the lowest observed NH winter lower stratospheric temperatures, and the latest observation of HN temperatures below the type 2 PSC threshold.